Shining a light on hidden PFAS: Development of a UV-reducible organic fluorine assay for the rapid screening of PFAS in AFFF, water, soils, and commercial products - David Patch; Natalia O’Connor; Ellie Ahmed; Erika Houtz; Michael J. Bentel; Ian Ross; Jennifer Scott; Iris Koch; Kela Weber (Journal of Hazardous Materials, 2025)

Advancing PFAS characterization: Development and optimization of a UV-H2O2-TOP assay for improved PFCA chain length preservation and organic matter tolerance - David Patch; Natalia O'Connor; Ellie Ahmed; Erika Houtz; Michael Bentel; Ian Ross; Jennifer Scott; Iris Koch; Kela Weber (Science of The Total Environment, 2024)

Transport parameters for PFOA and PFOS migration through GCL's and composite liners used in landfills - Farah B. Barakat; R. Kerry Rowe; David Patch; Kela Weber (Geotextiles and Geomembranes, 2024)

Occurrence and mobility of thiolated arsenic in legacy mine tailings - Jaabir D. Ali; Adriana Guatame-Garcia; Heather E. Jamieson; Michael B. Parsons; Matthew I. Leybourne; Iris Koch; Kela P. Weber; David J. Patch; Anna L. Harrison; Bas Vriens (Science of The Total Environment, 2024)

Mechanochemical degradation of per- and polyfluoroalkyl substances in soil using an industrial-scale horizontal ball mill with comparisons of key operational metrics - Nicholas Battye; David Patch; Iris Koch; Ryan Monteith; Dylan Roberts; Natalia O'Connor; Bernard Kueper; Michael Hulley; Kela Weber (Science of The Total Environment, 2024)

Advancing PFAS characterization: Enhancing the total oxidizable precursor assay with improved sample processing and UV activation - David Patch; Natalia O'Connor; Taylor Vereecken; Daniel Murphy; Gabriel Munoz; Ian Ross; Caitlin Glover; Jennifer Scott; Iris Koch; Sébastien Sauvé; Jinxia Liu; Kela Weber (Science of The Total Environment, 2024)

Elucidating the relationship between PFOA and PFOS destruction, particle size and electron generation in amended media commonly found in soils - Lauren P. Turner; Bernard H. Kueper; David J. Patch; Kela P. Weber (Science of The Total Environment, 2023)

Forever no more: Complete mineralization of per- and polyfluoroalkyl substances (PFAS) using an optimized UV/sulfite/iodide system - Natalia O'Connor; David Patch; Diana Noble; Jennifer Scott; Iris Koch; Kevin G. Mumford; Kela Weber (Science of The Total Environment, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Bumble bees exhibit daily behavioral patterns in pollen foraging - Anthony D. Vaudo; Harland M. Patch; David A. Mortensen; Christina M. Grozinger; John F. Tooker (Arthropod-Plant Interactions, 2014)

The costimulatory genes Cd80 and Cd86 are linked on mouse chromosome 16 and human chromosome 3 - Roger H. Reeves; David Patch; Arlene H. Sharpe; Frank Borriello; Gordon J. Freeman; Susanne Edelhoff; Christine Disteche (Mammalian Genome, 1997)